Sosialisasi Aspek Hukum dan Psikologi Terhadap Judi Online dan Pinjaman Online Bagi Generasi Muda di Kecamatan Sunggal - Zulyadi, Rizkan; Munawir S, Zaini; Hasmayni, Babby (Nanggroe: Jurnal Pengabdian Cendikia, 2025)
This community service activity carried out by the young generation of Krio village, Sunggal District, North Sumatra aims to provide education on the Legal and Psychological Aspects of Online Gambling and Online Loans and the impact of online gambling and online loans on the future and mental health of the Young Generation. Providing an understanding of the importance of always being alert to the enticements and enticements of online gambling. Gambling is a criminal act that involves risking a certain amount of money where the winner will get all the money used as betting material. Gambling can harm society and damage the nation's morals. The rise of online gambling among the younger generation can be influenced by economic and environmental factors. The impact of gambling on financial management includes being wasteful, addictive, online gambling has many negative impacts. Among them are the social impact, namely lazy socializing, the material impact, namely if they lose, their money will run out, the religious impact, namely they will neglect worship because they play online gambling, as well as the achievement impact, namely their study and work achievements will decrease because they are lazy due to online gambling and online loans.